Efficacy of intranasal insulin in improving cognition in mild cognitive impairment or dementia: a systematic review and meta-analysis - Long, Cong; Han, Xuke; Yang, Yunjiao; Li, Tongyi; Zhou, Qian; Chen, Qiu (Frontiers in Aging Neuroscience, 2022)
Background Insulin regulates many aspects of brain function related to mild cognitive impairment (MCI) or dementia, which can be delivered to the brain center via intranasal (IN) devices. Some small, single-site studies indicated that intranasal insulin can enhance memory in patients with MCI or dementia. The pathophysiology of Alzheimer's disease (AD) and diabetes mellitus (DM) overlap, making insulin an attractive therapy for people suffering from MCI or dementia. Objective The goal of the study is to evaluate the effectiveness of IN insulin on cognition in patients with MCI or dementia. Methods We searched the electronic database for randomized controlled trials (RCTs) that verified the effects of insulin on patients with MCI or dementia.16 studies (899 patients) were identified. Results The pooled standard mean difference (SMD) showed no significant difference between IN insulin and placebo groups; however, statistical results suggested a difference between study groups in the effects of ADCS-ADL; AD patients with APOE4 (-) also showed improved performance in verbal memory; other cognitions did not improve significantly. Conclusion In view of IN insulin's promising potential, more researches should be conducted at a larger dose after proper selection of insulin types and patients. Systematic review registration http://www.crd.york.ac.uk/PROSPERO/, identifier CRD42022353546.